Pesquisa de Salmonella e das condições sanitárias em frangos e lingüiças comercializados na cidade de Botucatu - Rall, Vera Lúcia Mores [UNESP] (2009)
In the present investigation were evaluated the sanitary conditions of poultry and several types of sausages retailed in Botucatu, São Paulo, Brazil for the determination of the most probable number of coliforms at 45°C/g besides the research of Salmonella using traditional methodology and PCR. In order to do so, 50 samples of poultry and 75 of sausages were collected from nine different establishments in the city, in the period of April to November of 2006. Of the 50 samples of chicken meat, 35 (70%) were out of the microbiologic parameters, according to Brazilian Sanitary Resolution RDC no 12 of Anvisa (>104 coliforms at 45°C/g). In this Resolution, the research of Salmonella is not demanded, but 4 samples (8%) presented the pathogen using the traditional methodology. That presence was confirmed by PCR, which was also positive in another 23, in a total of 27 positive samples (54%). Among 75 samples of sausages, 30 (40%) were out of the allowed limits, with 7 positive samples for Salmonella, using traditional methodology. However, if we consider PCR test, the number of positive samples increases to 42 (56%). Adding this number to coliforms microbiological limits, 86.7% of the analyzed sausages were inappropriate for the consumption.